Non‐Fourier Boundary Conditions Effects on the Skin Tissue Temperature Response. Issue 1 (7th September 2015) - Forghani, P.; Ahmadikia, H.; Karimipour, A.
Abstract : Thermal wave and dual phase lag bioheat transfer equations are solved analytically in the skin tissue exposed to oscillatory and constant surface heat flux. Comparison between the application of Fourier and non‐Fourier boundary conditions on the skin tissue temperature distributions is studied. The amplitude of temperature responses increases and also the phase shift between the temperature responses and heat flux decreases under the non‐Fourier boundary conditions for the case of an oscillatory surface heat flux. It is supposed the stable temperature cycles in order to estimate the blood perfusion rate via the existing phase shift between the surface heat fluxes and the temperature responses. It is shown that the higher rates of the blood perfusion correspond to lower phase shift between the surface temperature responses and the imposed heat flux.